Impact of Empowering Leadership on Using Enterprise Resource Planning System: The Mediating Role of Users’ Attitudes and Computer Anxiety - Ababneh, Hayel T.; Banikhaled, Abeer A. (Jordan Journal of Business Administration, 2024)
This study aims to identify the level of using the ERP system when adopting the empowering leadership style in Jordan private hospitals. This study attempts to explore the impact of empowering leadership on the use of the ERP system through the anxiety of using computers and the attitude of employees towards using ERP. To test the study hypotheses, data was collected by a questionnaire that was distributed electronically to (6) private hospitals that apply the ERP system. The study sample consisted of (106) employees in private hospitals. Data was analyzed through PLS software using structural-equation modeling (SEM). One of the most important results of this study is that empowering leadership has no effect on computer anxiety and that employee anxiety has no effect on the use of the ERP system. However, empowering leadership is positively influencing the employees' attitude towards ERP. It was also found that positive attitude towards the ERP system influences the use of the system. Additionally, the study revealed that empowering leadership has a direct effect on the use of the ERP system and an indirect effect on the use of the ERP system through computer anxiety and employee attitudes towards the ERP system. The researchers recommend studying the acceptance and use of the ERP system in other sectors.